Stories of sports critical literacy in media production, consumption, and dissemination - Garland, Katherin; Dredger, Katie Shepherd; Beach, Crystal L.; Leogrande, Cathy (Lexington Books, 2021)
"This book centralizes media, sports, and athlete identity while providing an in-depth evaluation of the role that media play in how society views and discusses sports and athletes, highlighting several types of intertextuality and intersectionality while doing so"--